Speed adaptation in cycle duration and emg during running at different terrain and ground conditions - Nilsson, J.; Gjerset, A.; Johansen, E.; Lund, M. (LASE Journal of Sport Science, 2014)
The purpose was to study how important stride parameters such as the cycle duration, electromoygraphical (EMG) burst duration and activation level change with running speed and with change in terrain and ground conditions. In total six male regional to national level elite orienteers participated in the study. Mean (range), height and weight were 25 (19-32) years, 180 (1.74-1.88)m and 71 (67-75)kg. Hip joint angular displacement was determined by means of an electrogoniometer. The electrical activity in m. vastus lateralis (VL) of the right leg was recorded with bipolar surface electrodes taped over the belly of the muscles. Electrogoniometric and EMG data were recorded by means of a portable data logger at a rate of 1000 Hz. The time between markers in test intervals was recorded by means of an ultra sound based timing system (Time-it, Eleiko AB, Sweden). The participating orienteers performed, after a warming up period, runs on four different horizontal ground surfaces; gravel road, forest terrain (low density undergrowth), timber felling and wet moss. The recordings were done during running in four different constant self determined speeds: slow, medium, fast (competition speed) and maximum speed. The cycle duration decreased in a similar manner with speed during running in all the tested terrain conditions and gravel road. The burst duration of the knee extensor m. vastus lateralis showed the same trend as the change in cycle duration with speed. The same increasing trend in mean EMG activation level with speed is seen in all terrain conditions and gravel road. However, specific differences between terrain and surface conditions in cycle duration, burst duration and EMG amplitude were present.